2004
DOI: 10.1021/jp049500v
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Lateral Charge Propagation in [Os(bpy)2(PVP)nCl]Cl Thin Films: A Scanning Electrochemical Microscopy Approach

Abstract: The use of scanning electrochemical microscopy (SECM) to measure charge transport diffusion constants (D CT ) in metallopolymers of the type [Os(bpy) 2 (PVP) n Cl]Cl, bpy ) 2,2′-bipyridyl and PVP ) poly(4vinylpyridine), is described. In this approach, a triple potential step technique is employed in which the ultramicroelectrode (UME) tip of the SECM is used to electrogenerate a solution phase oxidant, Ru(CN) 6 3-, in an initial potential step, via the oxidation of Ru(CN) 6 4-. This moiety diffuses from the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 55 publications
1
57
0
1
Order By: Relevance
“…The electrochemistry of thick drop cast films electrodes similar to the one presented in this work shows a D eh in the order of 10 À11 cm 2 s À1 [14], while for thin films its value is in the order of 10 À9 cm 2 s À1 [11,15].Taking into account this two situations, we found that using the diffusion coefficient obtained by Calvo et al [11] is possible to reproduce with a great accuracy the experimental results (Figure 2), showing an efficient electron hopping behavior and the fact that the observed behavior is a consequence of the thickness of the film. This value was also used for Flexer et al [12] to simulate a self-assembled system using a similar electroactive polyelectrolyte.…”
Section: Resultsmentioning
confidence: 76%
“…The electrochemistry of thick drop cast films electrodes similar to the one presented in this work shows a D eh in the order of 10 À11 cm 2 s À1 [14], while for thin films its value is in the order of 10 À9 cm 2 s À1 [11,15].Taking into account this two situations, we found that using the diffusion coefficient obtained by Calvo et al [11] is possible to reproduce with a great accuracy the experimental results (Figure 2), showing an efficient electron hopping behavior and the fact that the observed behavior is a consequence of the thickness of the film. This value was also used for Flexer et al [12] to simulate a self-assembled system using a similar electroactive polyelectrolyte.…”
Section: Resultsmentioning
confidence: 76%
“…Measurable effects on this electrochemical signal are only possible when the probe and the substrate are close to each other, for example, to a distance shorter than about five times the UME radius where their diffusion layers can interact; a typical UME has a radius close to 10 mm or smaller. The electrogenerated species may be reactive towards chemical species at the substrate; thus, the feedback mode has been applied to study the heterogeneous reactivity, for instance, from mediators that "micro titrate" chemisorbed species at electrodes, [5,6] that chemically etch metals [7] involved in the study of the effects of mediator surface diffusion, [8][9][10] lateral charge propagation in polymer films, [11,12] and diffusion in monolayers, [13] as well as used in the detection of reactive species in living cells. [14] In these examples, the SECM probe acts both as a generator of the reactive species and as a transducing element as the feedback current indicates the existence and extent of chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[62] A value of 6-8 10 À10 cm 2 s À1 has been reported for [Os(bpy) 2 -(PVI) 10 Cl] (PVI: polyvinyl-imidazol) (from CV). [63] The charge diffusion coefficients for an osmium-bipyridine redox couple embedded in Nafion and PSS has been reported to be 0.7 10 À10 [26] and 5 10 À9 cm 2 s À1 , [64] respectively.…”
mentioning
confidence: 96%
“…The large spread of D app values reported for similar systems can be ascribed to the measuring technique. [62] Stationary techniques (such as EIS) yield larger D app values than techniques involving complete oxidation/reduction (i.e. CV) because they do not require ion fluxes and/or polymer rearrangements.…”
mentioning
confidence: 99%